Dominasi Oligarki dan Praktik State Capture dalam Konflik Masyarakat Adat dengan PT Toba Pulp Lestari (TPL) - Hidayat, Yayan (Journal of Politics and Policy, 2024)
The conflict between Indigenous Peoples and P. Toba Pulp Lestari (PT TPL) has been going on for more than three decades and has not led to a resolution. The practice of state capture and oligarchy in PT TPL conflict with Indigenous Peoples dominates almost all conflicts. The political network and material power that PT TPL has with the Government have strengthened the company's existence. The aim of this research is to identify the relationship between the Oligarchy and the State in the conflict between Indigenous Peoples and PT TPL. This research uses qualitative methods with case studies to dissect complex and dynamic relationship patterns in this conflict. This research found that there had been bartering of the interests of the State and the Oligarchy in the TPL case. The diversity of material power they possess makes the oligarchy politically significant in 'controlling' state policy.